A comparision study on the effectiveness of advertising creative styles. - Kwek, Mingda. (2008)
This is a qualitative report on the comparison between the effectiveness of two different advertising creative styles. Local and international advertisers who are vying for a share of the advertising dollars can benefit by understanding the target country’s perception towards different creative styles and its influence in consumer’s buying intentions. Our findings will help guide advertisers and marketers in creating effective execution techniques in advertising, through the study of the two widely used advertising creative styles in Singapore.